2002
DOI: 10.1101/lm.50002
|View full text |Cite
|
Sign up to set email alerts
|

Intrahippocampal Wortmannin Infusion Enhances Long-Term Spatial and Contextual Memories

Abstract: The transition from short-to long-term memory involves several biochemical cascades, some of which act in an antagonistic manner. Post-training intrahippocampal administration of wortmannin, a pharmacological inhibitor of phosphatidylinositol 3-kinase, had no effect on memory tested 3 h later, but improved long-term memory tested 48 h following the completion of training. This effect was seen in two hippocampus-dependent tasks: the Morris water maze, using both massed and distributed training paradigms, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…Therefore, mTOR regulates protein turnover in neurons by functioning at the intersection between protein synthesis and degradation. Pharmacological reagents, such as rapamycin or WRT, modulate mTOR activity and are known to have roles in synaptic plasticity and memory (Dash et al, 2002;Cammalleri et al, 2003;Hoeffer et al, 2008). Their effects have been explained only on the basis of local translation, although these reagents are common autophagy modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mTOR regulates protein turnover in neurons by functioning at the intersection between protein synthesis and degradation. Pharmacological reagents, such as rapamycin or WRT, modulate mTOR activity and are known to have roles in synaptic plasticity and memory (Dash et al, 2002;Cammalleri et al, 2003;Hoeffer et al, 2008). Their effects have been explained only on the basis of local translation, although these reagents are common autophagy modulators.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K has been implicated in the acquisition of long-term fear memory. 290,291 Studies employing measurement of pAkt levels within the BLA following extinction training have produced very inconsistent results. Cannich et al 288 reported no significant increase in pAkt in the BLA of extinguished wild-type or cannabinoid receptor knockout (CB1À/À) mice relative to nonextinguished controls, although the ratio of pAkt levels in extinguished vs nonextinguished animals was significantly greater in the knockouts (which exhibit a profound extinction impairment) than in the wild types.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…Additionally, trkB KI mutants with blocked activation of PI3K/Akt signaling have impaired cued fear LTM formation, while contextual fear LTM is spared (Musumeci et al 2009). Further, hippocampal PI3K/Akt signaling is not known to have a role in spatial memory formation (Dash et al 2002;Horwood et al 2006;Chao et al 2007). Thus, in the amygdala PI3K/Akt signaling is important for LTM formation, while this pathway may not be required for hippocampal LTM formation.…”
Section: Pi3kmentioning
confidence: 99%